Oral History Program Interview: Edgar Romine Crane - Crane, Edgar Romine
Crane was born in Haskell, Haskell County, Texas in 1910. His interview includes his arrival in Shafter, California on December 24, 1930, comments regarding labor and government camps, the Cherokee Strip housing development, transient and established workers' living conditions, benefits of WPA and CCC, his rejection to unions and strikes, Californians discouraging influx of migrants, how The Grapes of Wrath is based on true facts, big farms taking advantage of workforce, farmworker race relations, the lack of hostility towards migrants, why he finds "Okie" unintentionally demeaning, and thoughts on government loans from SRA relief.